The bigwig Project - Brabrand, Claus; Møller, Anders; Schwartzbach, Michael I. (BRICS Report Series, 2000)
We present the results of the -bigwig- project, which aims to design and implement a high-level domain-specific language for programming interactive Web services. The World Wide Web has undergone an extreme development since its invention ten years ago. A fundamental aspect is the change from static to dynamic generation of Web pages. Generating Web pages dynamically in dialogue with the client has the advantage of providing up-to-date and tailor-made information. The development of systems for constructing such dynamic Web services has emerged as a whole new research area. The <bigwig> language is designed by analyzing its application domain and identifying fundamental aspects of Web services. Each aspect is handled by a nearly independent sublanguage, and the entire collection is integrated into a common core language. The -bigwig- compiler uses the available Web technologies as target languages, making -bigwig- available on almost any combination of browser and server, without relying on plug-ins or server modules.